(untitled) (REMUNOM, 2024)
Economic evaluation of medicines plays a crucial role in the face of the growing variety and complexity of available treatments, providing a robust analytical framework to assist healthcare managers in the challenging task of resource allocation. In a scenario where health demands compete directly with limited financial resources, economic evaluation becomes essential in informing strategic decisions. The fundamental principles of economic evaluation include systematically comparing the costs associated with different medical interventions to the benefits achieved in terms of health and quality of life. The cost-effectiveness approach, for example, focuses on calculating the additional cost needed to achieve a specific benefit, such as gained life-years. In contrast, cost-utility analysis goes further by integrating quality of life measures to quantify quality-adjusted life years (QALYs), allowing for a more comprehensive comparison between interventions that impact health in different ways. These methods not only guide the selection of therapies that offer the best return on investment in public health but also help ensure that resources are efficiently directed to maximize health outcomes for the population. Furthermore, the application of these analyses may vary depending on the local context, taking into account specific demographic, epidemiological, and economic characteristics of each region. Therefore, economic evaluation is not just a technical tool but also a crucial component in formulating equitable and sustainable health policies, contributing to effective resource management in the healthcare sector and continuous improvement in access to and quality of medical care available to the population."